Functional recovery with peripheral nerve block versus general anesthesia for upper limb surgery: a systematic review - Jennifer Héroux; Pierre-Olivier Bessette; Emilie Belley-Côté; Daphnée Lamarche; Pablo Échavé; Marie-Josée Loignon; Nicolas Patenaude; Jean-Patrice Baillargeon; Frédérick D’Aragon (BMC Anesthesiology, 2023)
Abstract Background Peripheral nerve block is a common anesthetic technique used during orthopedic upper limb surgery. Injection of local anesthetics around the target nerve inhibits the action of voltage-dependent sodium channels, inhibiting neurotransmission of pain impulses and providing motor immobility. Compared to general anesthesia, it could improve functional recovery by inhibiting nociceptive impulses and inflammation, thus reducing postoperative pain and immobilization and improving postoperative rehabilitation. This systematic review evaluates the impact of peripheral nerve block versus general anesthesia on postoperative functional recovery following orthopedic upper limb surgery. Methods We searched CENTRAL, MEDLINE, CINHAL, EMBASE, and Scopus trial databases from inception until September 2021 for studies comparing peripheral nerve block to general anesthesia. We collected data on functional recovery, range of motion, patient satisfaction, quality of life, and return to work. We pooled studies using a random-effects model and summarized the quality of evidence with the GRADE approach. Results We assessed 373 citations and 19 full-text articles for eligibility, and included six studies. Six studies reported on functional recovery, but failed to detect a significant superiority of peripheral nerve block over general anesthesia (3 RCT studies, N = 160; SMD -0.15; CI at 95% -0.60–0.3; I2 = 45%; p = 0.07; low quality of evidence and 3 observational studies, N = 377; SMD -0.35; CI at 95% -0.71–0.01; I2 = 64%; p = 0.06; very low quality of evidence). Conclusions Current literature is limited and fails to identify the benefit of peripheral nerve block on functional recovery. More studies are needed to assess the impact on long-term recovery. Considering the potential impact on clinical practice and training, a prospective study on functional recovery is ongoing (NCT04541745). Trial registration PROSPERO ID CRD42018116298. Registered on December 4, 2018.